2018
DOI: 10.1080/21663831.2018.1461141
|View full text |Cite
|
Sign up to set email alerts
|

Strong and ductile medium Mn steel without transformation-induced plasticity effect

Abstract: The conventional alloy design of medium Mn steel is to optimize the transformation-induced plasticity (TRIP) effect. Here we show that a dual-phase heterogeneous structure is sufficient to develop a medium Mn steel with high yield strength ( ∼ 1.2 GPa) and large uniform elongation ( ∼ 14.5%). The ultra-high strength is contributed by high back-stress while the large ductility is induced by strain-gradient plasticity and back-stress hardening, both of which are inherent to dual-phase heterogeneous structure. TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Pioneering studies have shown that pure Ti with a heterogeneous lamella structure can unite UFG strength and coarse-grain ductility 19 . Such combinations of high strength and good ductility were also demonstrated recently in an interstitial free (IF) steel 20 and a Mn steel 21 . Therefore, the present study is aimed to produce a layered bimodal grain structure in Mg alloys and address the effect of bimodal structures on mechanical properties.…”
Section: Introductionsupporting
confidence: 57%
“…Pioneering studies have shown that pure Ti with a heterogeneous lamella structure can unite UFG strength and coarse-grain ductility 19 . Such combinations of high strength and good ductility were also demonstrated recently in an interstitial free (IF) steel 20 and a Mn steel 21 . Therefore, the present study is aimed to produce a layered bimodal grain structure in Mg alloys and address the effect of bimodal structures on mechanical properties.…”
Section: Introductionsupporting
confidence: 57%
“…The partitioned stress/strain is a vital extrinsic factor in affecting the austenite stability and is correlated to the strength of adjacent phases. If the partitioned stress does not effectively increase the mechanical interaction energy to help the austenite grains overcome the nucleation barrier, the TRIP effect resulting from the martensitic transformation may be suppressed during the plastic deformation [ 205 ]. In this case, the improvement of work hardening behaviors assisted by the TRIP effect is missed, leading to the relatively low work hardening rate.…”
Section: Alloy Design Strategiesmentioning
confidence: 99%
“…Medium- and high- Mn steels are the most promising candidates with the TRIP effect and thus show excellent mechanical properties. The strengthening mechanism for those materials is based on the transformation of the metastable austenite induced by deformation, i.e., the face-centered cubic (FCC) structured γ-phase characterized by a high work hardening capacity to achieve very high strength together with exceptional ductility 1 to martensite characterized by the hexagonal close-packed (HCP) ε-phase and/or body-centered cubic (BCC) α′-phase 27 .…”
Section: Introductionmentioning
confidence: 99%